The adverse role of endocrine disrupting chemicals in the reproductive system - Pan, Jing; Liu, Pengfei; Yu, Xiao; Zhang, Zhongming; Liu, Jinxing (Frontiers in Endocrinology, 2024)
Reproductive system diseases pose prominent threats to human physical and mental wellbeing. Besides being influenced by genetic material regulation and changes in lifestyle, the occurrence of these diseases is closely connected to exposure to harmful substances in the environment. Endocrine disrupting chemicals (EDCs), characterized by hormone-like effects, have a wide range of influences on the reproductive system. EDCs are ubiquitous in the natural environment and are present in a wide range of industrial and everyday products. Currently, thousands of chemicals have been reported to exhibit endocrine effects, and this number is likely to increase as the testing for potential EDCs has not been consistently required, and obtaining data has been limited, partly due to the long latency of many diseases. The ability to avoid exposure to EDCs, especially those of artificially synthesized origin, is increasingly challenging. While EDCs can be divided into persistent and non-persistent depending on their degree of degradation (Lee Y M et al., 2018), due to the recent uptick in research studies in this area, we have chosen to focus on the research pertaining to the detrimental effects on reproductive health of exposure to several EDCs that are widely encountered in daily life over the past six years, specifically bisphenol A (BPA), phthalates (PAEs), polychlorinated biphenyls (PCBs), parabens, pesticides, heavy metals, and so on. By focusing on the impact of EDCs on the hypothalamic-pituitary-gonadal (HPG) axis, which leads to the occurrence and development of reproductive system diseases, this review aims to provide new insights into the molecular mechanisms of EDCs' damage to human health and to encourage further in-depth research to clarify the potentially harmful effects of EDC exposure through various other mechanisms. Ultimately, it offers a scientific basis to enhance EDCs risk management, an endeavor of significant scientific and societal importance for safeguarding reproductive health.